Morphological variability of lateral femoral cutaneous nerve and its potential clinical significance - Kinga Włudyka; Nicol Zielinska; R. Shane Tubbs; Krystian Maślanka; Andrzej Borowski; Marek Drobniewski; Łukasz Olewnik (Folia Morphologica)
BACKGROUND: The lateral femoral cutaneous nerve is derived from the dorsal branches of the L2 and L3 spinal nerves. It travels across the pelvis and heads towards the anterior superior iliac spine. It passes under the lateral part of the inguinal ligament and then divides into 2 branches, which are responsible for sensory innervation of the anterolateral and lateral skin of the thigh. However, the course of this nerve can vary morphologically. Numerous differences have been observed in its exit from the pelvis and in the number of its main trunks and branches. Additionally, its angle with the inguinal ligament and its placement in relation to other structures (such as the femoral artery, femoral nerve, and the sartorius and iliacus muscles) also vary. All these variants have potential clinical implications. Therefore, the aim of this review is to present the morphological variability of the lateral cutaneous nerve and to explore how these anatomical differences can introduce clinical concerns. MATERIALS AND METHODS: The presented review of the literature was based on over 30 studies. A comprehensive literature search was done using PubMed to study the morphological variability of lateral femoral cutaneous nerve (LFCN). To be included in this review studies needed to meet certain criteria: published before December 2023, and presenting information valuable to this paper (variability of lateral femoral cutaneous nerve/clinical significance). The search included how LFCN vary among foetuses and adults with the aim of providing more complex information about the variability of this nerve. During the search, key words as follows were used. No references were excluded from the analysis. All relevant studies were included, and citation tracking was used to identify publications. RESULTS: This review presents a description of the variability of the LFCN and its potential clinical impact. In the review differences in adult and foetuses were considered, and morphological variability was divided into 4 groups: the origin of the nerve; the way it leaves the pelvis; the branching pattern; and the angle between LFCN and surrounding structures. Then the clinical significance was considered, based on available literature.